menu
QAmmunity.org
Login
Register
My account
Edit my Profile
Private messages
My favorites
Register
Ask a Question
Questions
Unanswered
Tags
Categories
Ask a Question
Let f(x) = 9x − 2 and g(x) = −x + 3. Find f(g(x)).
asked
Feb 25, 2016
199k
views
5
votes
Let f(x) = 9x − 2 and g(x) = −x + 3. Find f(g(x)).
Mathematics
high-school
Purag
asked
by
Purag
7.9k
points
answer
comment
share this
share
0 Comments
Please
log in
or
register
to add a comment.
Please
log in
or
register
to answer this question.
2
Answers
5
votes
f(g(x))=9(-x+3)-2
So: f(g(x)=-9x+27-2=-9x+25
PHeiberg
answered
Feb 27, 2016
by
PHeiberg
7.8k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
2
votes
f(x) = 9x - 2
g(x) = -x + 3
f(g(x)) = 9(-x + 3) - 2
f(g(x)) = 9(-x) + 9(3) - 2
f(g(x)) = -9x + 27 - 2
f(g(x)) = -9x + 25
Fbede
answered
Mar 2, 2016
by
Fbede
7.8k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
Ask a Question
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.
9.5m
questions
12.2m
answers
Other Questions
What is .725 as a fraction
How do you estimate of 4 5/8 X 1/3
A bathtub is being filled with water. After 3 minutes 4/5 of the tub is full. Assuming the rate is constant, how much longer will it take to fill the tub?
i have a field 60m long and 110 wide going to be paved i ordered 660000000cm cubed of cement how thick must the cement be to cover field
Write words to match the expression. 24- ( 6+3)
Twitter
WhatsApp
Facebook
Reddit
LinkedIn
Email
Link Copied!
Copy
Search QAmmunity.org